Analisis Sistem Informasi Manajemen Keluarga Miskin (SIMGAKIN) dalam Proses Pengambilan Keputusan Kebijakan Dinas Pendidikan dengan Kegiatan Pemberian Fasilitasi Sumbangan Pembinaan Pendidikan (SPP) Siswa Miskin yang Bersekolah Swasta di Kota Semarang - Santoso, Firmando; Djumiarti, Titik; Rihandoyo, Rihandoyo (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
The analysis of management information System Poor Family (SIMGAKIN) is one form of utilization of electronic governance. The application of SIMGAKIN in Local Development Planning Agency (Bappeda) at Semarang city, needed budgets, facilities and infrastructure/availability of technology, human resource management, and integration among other institution. Departement of Education is one user of SIMGAKIN for decision-making process. Research methodology descriptive with a qualitative approach used in this research to identify the development of SIMGAKIN and decision-making process. The result of the research showed that influence the stage of decision making in the implementation of activities by giving SPP facilities to needy students, related to the management of SIMGAKIN, that is oriented to decision, availability of technology, human resource management, communication systems, and integration, while in the decision-making is comprehension, planning or design, and selection. Oriented to decision of the SIMGAKIN, have been applied poor data collection service that's fast and accurate. Availability of technology to apply database, hardware, software, branware is still inadequate. In the implementation of SIMGAKIN Has been applied Training and development in accordance with the main main task and fungtion employees. Comunication system has been well-executed. Integration of BAPPEDA with other institutions, can be seen from the cooperation and planning programmed. Therefore comprehension, planning or design, and selection has been exploit the SIMGAKIN but still uses a long of activities. Based on the result this research recommends, need to be improve of poor data collection. Need to be improved SIMGAKIN application. Improving the quality and quantity of employees. Decision making by the selection new activities to maximize the fungtion and role of SIMGAKIN.